Rough metaphysics: the speculative thought and mediumship of Jane Roberts - Skafish, Peter (University of Minnesota Press, 2023)
Cover Page -- Title Page -- Copyright Page -- Contents -- Introduction. The Channel and the Philosopher -- Part I. Ontological Redistribution -- Chapter 1. Idea Construction -- Chapter 2. An Experience in Concepts -- Chapter 3. Distributions and Transformations -- Chapter 4. Translating Thought -- Part II. Alternatives of Metaphysics -- Chapter 5. The System of Aspects -- Chapter 6. The High Intellect: Thought in Variation -- Conclusion: Noetic Power, Psychical Politics -- Acknowledgments -- Notes -- Bibliography -- Index -- About the Author.